(untitled) (International journal of artificial intelligence, 2025)
Simultaneous interpretation is a crucial linguistic practice that enables real-time communication across different languages, playing a key role in diplomacy, international business, and global conferences. Unlike consecutive interpretation, where the speaker pauses for translation, simultaneous interpretation occurs in real time, requiring interpreters to listen, process, and translate messages almost instantaneously. This article explores the significance of simultaneous interpretation in bridging language barriers, the cognitive skills required for interpreters, and the challenges they face, such as maintaining accuracy, handling stress, and adapting to various speech patterns. Additionally, the impact of technology, including AI-assisted interpretation tools, on the future of this profession is discussed. As globalization accelerates, the demand for highly skilled simultaneous interpreters continues to rise, making it an indispensable profession in multilingual communication.